Reward sensitivity and hazardous alcohol consumption in women: The parallel mediation effect of self-control and impulsivity traits - Martín-Pérez, Cristina; Vergara-Moragues, Esperanza; Fernández-Muñóz, Juan José; García-González, Juan Manuel; García-Moreno, Luis Miguel (Substance Abuse, 2023)
Introduction: Little research has been carried out on the associations between several individual factors and hazardous alcohol use in women. The aim of this study was first, to study the relationship between reward sensitivity (RS) and alcohol use in both women with and without hazardous drinking separately. Second, to explore the potential mediating roles of the impulsivity and self-control traits in this relationship. Method: The study was analytical and cross-sectional and included 645 female participants (mean age = 19.14; standard deviation (SD)=1.60). All women were divided into two groups (286, 44.3%, with hazardous drinking, HDW; and 359, 55.7%, with light drinking, LDW). Correlation analyses were carried out to explore the associations between the variables, and parallel mediation analyses were performed to investigate the potential mediating roles of impulsivity and self-control in the RS-alcohol use associations in each group separately. Results: A significant association was observed between RS and alcohol use in HDW, contrary to that observed in their counterparts. In addition, both higher impulsivity and less self-control mediated the association between RS and alcohol use only in HDW. Conclusions: Impulsivity and self-control differently affect alcohol use under the condition of high reward sensitivity, only in HDW, suggesting alterations of the dual top-down and bottom-up mechanisms and a possible imbalance between the competing reflexive and impulsive brain systems. More research is needed regarding the individual factors that affect women's drinking to develop sensitive measures for the assessment of alcohol use and more efficient interventions for women.
Keywords: women; alcohol drinking; impulsive behavior; self-control; JCR; Scopus